2015
DOI: 10.1159/000381064
|View full text |Cite
|
Sign up to set email alerts
|

Dihydrotestosterone as a Protective Agent in Chronic Experimental Autoimmune Encephalomyelitis

Abstract: Multiple sclerosis is a chronic inflammatory disease affecting the central nervous system. As reported by clinical observations, variation in hormonal levels might alter disease susceptibility and progression. Specifically, decreased levels of testosterone in males are reported to be permissive for disease onset. Accordingly, testosterone seems to exert protective effects in experimental autoimmune encephalomyelitis (EAE). In this context, it is important to highlight that testosterone is further metabolized i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 79 publications
2
28
0
Order By: Relevance
“…Dihydrotestosterone has been effective in reducing the severity of chronic EAE in Dark Agouti rats (an experimental model showing a protracted relapsing EAE). Decreased gliosis and inflammation in the spinal cord has also been observed [96]. These results are in line with previous findings of Dalal et al [97] who reported a less severe course of EAE in dihydrotestosterone treated female SJL mice.…”
Section: Influence Of Gender and Sex Hormones On Eaesupporting
confidence: 92%
“…Dihydrotestosterone has been effective in reducing the severity of chronic EAE in Dark Agouti rats (an experimental model showing a protracted relapsing EAE). Decreased gliosis and inflammation in the spinal cord has also been observed [96]. These results are in line with previous findings of Dalal et al [97] who reported a less severe course of EAE in dihydrotestosterone treated female SJL mice.…”
Section: Influence Of Gender and Sex Hormones On Eaesupporting
confidence: 92%
“…Because some of the benefits of testosterone in EAE models may result from its aromatization to estradiol, testosterone preparations, as opposed to the downstream DHT product, have been initially explored. However, a recent study in EAE demonstrated a benefit of DHT, 51 obviating the need for further comparative studies.…”
Section: Testosterone As a Therapymentioning
confidence: 99%
“…Interestingly, even when excluding males from our study, the AR was still co-expressed with GJA1/Cx43. As androgens are known to prevent astrocytosis [29][30][31][32][33][34], our results raise the possibility that in males and females suffering from progressive forms of MS, activation of the AR is somehow defective and fails to downregulate a large set of progliotic genes induced by the TGFB/SMAD1/SMAD2 pathway. This could be due to an age-related decrease of circulating testosterone or of the circulating androgen precursors (Dehydroepiandrosterone and Androstendiol) that can be intracellularly metabolized into testosterone [54][55][56][57].…”
Section: Discussionmentioning
confidence: 79%
“…On the other hand, the androgen receptor (AR), which was also found to co-express with Cx43/GJA1, was previously shown to inhibit reactive astrocytosis under varied CNS conditions [29][30][31][32][33][34]. Of note, AR co-expressed also with Cx43/GJA1 when excluding the 2 male patients from our analysis (data supplement 3).…”
Section: A Unique Set Of Genes Co-upregulate With Cx43/gja1 In Periplmentioning
confidence: 85%